Numerical Simulation of Falling Film Absorption Process in the Vertical Tube with the Combination of Air and Water Cooling - 姜传胜; 王照亮; 李华玉; 金有海 (Zhileng xuebao)
The heat and mass coupled model was established together with the heat transfer equation in the annular for the combination of air and water cooling under the consideration of the effect of interfacial resistance, variable film thickness, transverse flow and the coolant on the absorption process. Falling film thickness, temperature, and concentration of the solution along the internal wall in the vertical tube were calculated. The effect of coolant inlet temperature, Re number and PE number of the solution on the heat transfer coefficient and absorption flux were analyzed. The results are in a good agreement with the experimental data. The results will be in favor of the design and optimization of the absorber with combination cooling.